The effects of moisture characteristics of Crushed Rock Base (CRB) - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (American Society of Civil Engineers (ASCE), 2011)
This paper reports the deformation behaviour of crushed rock with unsaturated condition under repeated cyclic loading triaxial (RLT) tests performed at different stress levels, in order to investigate the effect of moisture content to crushed rock performances and permanent deformation behaviour. Road surface rutting is the core basis of damage in flexible pavements which the mainly significant is crushed rock still unclearly thoughtful regarding deformation behaviour under real situation. RLT test is used to describe the various deformation responses of unbound granular materials (UGMs) by macro-mechanical observations. The main study focused on the influence of the moisture content. Moreover permanent deformation behaviour of crushed rock will be investigated and limit ranges of crushed rock should be considered in pavement analysis and design.